CoFe@Fe3O4 alloy CO2 hydrogenation catalyst with core-shell structure, preparation method and application thereof

By preparing the CoFe@Fe3O4 alloy catalyst with core-shell structure on a defect-rich carbon support, the problems of insufficient adsorption and activation capabilities of the existing CoFe alloy catalysts in the CO2 hydrogenation reaction are solved, and efficient and stable CO2 is achieved Conversion and CO selectivity.

CN115646492BActive Publication Date: 2025-02-18SHANGHAI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211328306.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-26
Publication Date
2025-02-18
Estimated Expiration
2042-10-26

AI Technical Summary

Technical Problem

The existing CO2 hydrogenation catalysts such as binary CoFe alloys have insufficient adsorption and activation capabilities in CO2 and H2, and are prone to sintering and agglomeration, which limits their efficiency and stability in CO2 hydrogenation reaction.

Method used

Using a CoFe@Fe3O4 alloy catalyst with a core-shell structure supported by defect-rich carbon, the CoFe@Fe3O4 alloy with a core diameter of 5-25nm and the Fe3O4 with a shell thickness of 1-5nm are prepared by heat treatment to ensure that the catalyst is uniformly loaded on the carbon support and avoid Sintered and reunited.

Benefits of technology

The high activity and stability of CoFe@Fe3O4 alloy catalyst in CO2 hydrogenation reaction was achieved, the CO2 conversion rate reached 30%, the CO selectivity reached 99%, and the cost was reduced, making it suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115646492B_ABST
    Figure CN115646492B_ABST
Patent Text Reader

Abstract

The present invention discloses a CoFe@Fe 3 O 4 Alloy CO 2 Hydrogenation catalyst, preparation method and application thereof, wherein the prepared catalyst core is a CoFe alloy with a diameter of 20nm and the shell is a Fe alloy with a thickness of 2nm 3 O 4 , uniformly loaded on the defect-rich carbon carrier, without sintering and agglomeration. In addition, the material of the present invention is used as a CO 2 The hydrogenation catalyst showed excellent catalytic activity at 450℃. 2 The conversion rate is 30%, the CO selectivity is 99%, and the material itself is pollution-free and easy to synthesize, and can be well applied in technical fields such as energy materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a CO2 hydrogenation catalyst and a preparation and application method thereof, and in particular to a defect-rich carbon-supported CoFe@Fe3O4 alloy catalyst with a core-shell structure and a preparation method thereof. Background Art

[0002] Fossil energy has brought huge energy for human survival and development. As of 2019, fossil energy accounts for 78.9% of the global energy system. Such a large amount of fossil energy combustion has caused energy depletion, and the CO2 gas emitted into the atmosphere has caused a serious greenhouse effect. Therefore, catalytic conversion of CO2 into clean energy is an effective measure to solve the energy and environmental crisis. However, CO2 is a non-polar linear molecule with a short carbon-oxygen bond distance, which makes the CO2 molecule very stable and difficult to convert directly. The introduction of H2 can reduce the Gibbs free energy of the overall reaction, allowing the reaction to occur under milder conditions. CO2 hydrogenation can produce many products, such as low-carbon alcohols, low-carbon olefins, dimethyl ether, low carbonic acid, methane, carbon monoxide, etc., among which methane and carbon monoxide can be obtained by reaction at normal pressure, and carbon monoxide and hydrogen can also be used as synthesis gas to synthesize high-value-added chemicals through subsequent Fischer-Tropsch reaction, which has been widely used in industry. Therefore, the reaction of CO2 hydrogenation to produce carbon monoxide (reverse water gas shift reaction) has important research value.

[0003] Precious metal catalysts such as platinum-based catalysts have high reactivity in CO2 hydrogenation reactions, but they often cannot have both high CO2 conversion and high CO selectivity (especially at high reaction temperatures), and are limited by the cost of precious metals, which limits their widespread use. Therefore, in recent years, researchers have shifted more attention to non-precious metal catalysts. Through reasonable structural and component design, their activity and selectivity can reach or even exceed the level of precious metal catalysts. Binary non-precious metal CoFe alloys are considered to be a promising CO2 hydrogenation catalyst, but binary CoFe alloys still have many problems, such as insufficient adsorption and activation of reaction gases (CO2 and H2), sintering and agglomeration, etc. Summary of the invention

[0004] In order to solve the problems of the prior art, the purpose of the present invention is to overcome the shortcomings of the existing technology and provide a CoFe@Fe3O4 alloy CO2 hydrogenation catalyst with a core-shell structure, a preparation method and an application thereof. The CoFe@Fe3O4 alloy particles are uniformly loaded on a defect-rich carbon carrier without sintering and agglomeration, so that the CoFe@Fe3O4 alloy composite material has high activity and stability in the CO2 hydrogenation reaction.

[0005] In order to achieve the above invention purpose, the present invention adopts the following technical solution:

[0006] A method for preparing a CoFe@Fe3O4 alloy CO2 hydrogenation catalyst with a core-shell structure, using CoFe2O4 and g-C3N4 as precursor materials and a heat treatment method to prepare a catalyst material of a CoFe alloy with a core diameter of 5-25nm and Fe3O4 with a shell thickness of 1-5nm supported on a defect-rich carbon carrier, as a catalyst material for CO2 hydrogenation reaction.

[0007] Preferably, a catalyst material having a core diameter of 20 nm CoFe alloy and a shell thickness of 2 nm Fe3O4 supported on a defect-rich carbon support is prepared.

[0008] Preferably, the method for preparing the CoFe@Fe3O4 alloy CO2 hydrogenation catalyst having a core-shell structure according to the present invention is characterized by comprising the following steps:

[0009] Step 1: Prepare Co using wet chemical method x Fe y O4, the molar ratio of the CoFe element prepared according to the target is (1-2): (2-1), where x is 1-2 and y is 1-2;

[0010] Step 2: Prepare g-C3N4 by thermal polymerization, and perform ultrasonic exfoliation on it with an ultrasonic power of 100-500W, centrifuge and take the supernatant to prepare layered g-C3N4;

[0011] Step 3: The Co prepared in step 1 x Fe y O4 is loaded on the layered g-C3N4 prepared in step 2, so that Co x Fe y The O4 loading is not higher than 30wt%, and g-C3N4 / Co x Fe y O4 composite materials;

[0012] Step 4: g-C3N4 / Co prepared in step 3 x Fe y The O4 composite material is annealed at a temperature of 300-600°C and cooled to room temperature to obtain a defect-rich carbon-supported CoFe@Fe3O4 alloy catalyst material with a core-shell structure.

[0013] Preferably, in step 1, no more than 2 mmol of cobalt acetylacetonate and no more than 2 mmol of iron acetylacetonate are weighed and ultrasonically dispersed in triethylene glycol; the mixed solution is heated to no more than 110° C. and kept warm for at least 30 min; then the temperature is raised to no more than 250° C. and kept warm for at least 60 min; then cooled to room temperature, washed by centrifugation with ethyl acetate and freeze-dried to obtain Co x Fe y O4.

[0014] Preferably, in the above step 2, at least 10 g of urea is weighed and placed in a 50 mL crucible, and the temperature is raised to not less than 550° C. at a heating rate of not less than 2.3° C. / min and kept warm for at least 4 hours to carry out a thermal polymerization reaction; the product is then ultrasonically stripped at an ultrasonic power of 100-500 W; the supernatant is then freeze-dried to obtain layered g-C3N4.

[0015] Preferably, in the above step 3, at least 100 mg of layered g-C3N4 is ultrasonically dispersed in deionized water; then 5-30 mg of Co is added. x Fe y O4, ultrasonic for 1h; freeze-dried to obtain g-C3N4 / Co x Fe y O4 composite material.

[0016] Preferably, in the above step 4, g-C3N4 / Co x Fe y O4 composite material is annealed in a mixture of CO2 and H2. Calculated by volume percentage, the H2 in the mixture is 25-50 vol%, the CO2 is 0-25 vol%, the balance gas is Ar, and the annealing temperature is 300-600°C. After annealing, a CoFe@Fe3O4 alloy catalyst material with a core-shell structure supported by defect-rich carbon is formed.

[0017] A CoFe@Fe3O4 alloy CO2 hydrogenation catalyst with a core-shell structure is prepared by using the preparation method of the CoFe@Fe3O4 alloy CO2 hydrogenation catalyst with a core-shell structure described in the present invention.

[0018] Preferably, the CoFe@Fe3O4 nanoparticles having a core-shell structure are uniform in size, and the CoFe@Fe3O4 nanoparticles are evenly distributed on the defect-rich carbon support to form a composite material structure.

[0019] An application of the CoFe@Fe3O4 alloy CO2 hydrogenation catalyst with a core-shell structure of the present invention is to use the CoFe@Fe3O4 alloy CO2 hydrogenation catalyst with a core-shell structure as a catalyst material for CO2 hydrogenation reaction. It is used in CO2 hydrogenation reaction and has extremely high reaction activity and stability.

[0020] Compared with the prior art, the present invention has the following obvious outstanding substantive features and significant advantages:

[0021] 1. The CoFe@Fe3O4 alloy catalyst with a core-shell structure supported by defect-rich carbon of the present invention has an excellent morphology and structure, wherein the core is CoFe alloy and the shell is Fe3O4. The CoFe@Fe3O4 is uniform in size and evenly distributed on the defect-rich carbon support, and no agglomeration and sintering occurs during the reaction;

[0022] 2. The defect-rich carbon-supported CoFe@Fe3O4 alloy catalyst with a core-shell structure exhibits extremely high catalytic reaction activity and stability in the catalytic reaction of CO2 hydrogenation, because the defect-rich carbon support and CoFe@Fe3O4 improve the adsorption and activation of CO2 and H2, respectively;

[0023] 3. The preparation process of the present invention is simple, low in cost, and can be industrialized. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The X-ray diffraction patterns of the materials synthesized in Examples 1-4 are shown in FIG.

[0025] Figure 2 The transmission electron microscope image and electron energy loss spectrum of Example 1 are shown.

[0026] Figure 3 This is the selected area electron diffraction pattern of Example 1.

[0027] Figure 4 This is the Raman graph of Example 1.

[0028] Figure 5 This is a performance diagram of the CO2 hydrogenation reaction of Examples 1-3. DETAILED DESCRIPTION

[0029] The above scheme is further described below in conjunction with specific implementation examples. The preferred embodiments of the present invention are described in detail as follows:

[0030] Example 1

[0031] In this embodiment, a method for preparing a defect-rich carbon-supported CoFe@Fe3O4 alloy catalyst having a core-shell structure comprises the following steps:

[0032] Step 1: Using a wet chemical method, 1 mmol (256 mg) of cobalt acetylacetonate and 1 mmol (353 mg) of iron acetylacetonate were ultrasonically dispersed in triethylene glycol; the mixed solution was heated to 110°C and kept warm for 30 minutes; then the temperature was raised to 250°C and kept warm for 60 minutes; finally, it was cooled to room temperature, washed by centrifugation with ethyl acetate and freeze-dried to obtain a sample CoFeO4 precursor material;

[0033] Step 2: Using the thermal polymerization method, 10 g of urea was placed in a 50 mL crucible, and the temperature was raised to 550 ° C at a rate of 2.3 ° C / min, and kept warm for 4 hours; then ultrasonic stripping was performed with an ultrasonic power of 300 W; the supernatant was freeze-dried to obtain layered g-C3N4;

[0034] Step 3: 100 mg of layered g-C3N4 was ultrasonically dispersed in deionized water; then 15 mg of the CoFeO4 precursor material obtained in step 1 was added, ultrasonicated for 1 h; freeze-dried to obtain a g-C3N4 / CoFeO4 composite material;

[0035] Step 4: anneal the material obtained in step 3 in a mixture of CO2 and H2, wherein the H2 in the mixture is 25 vol%, CO2 is 25 vol%, and the balance gas is Ar. The annealing temperature is 450°C and the temperature is kept for 1 hour. Cool to room temperature to obtain a defect-rich carbon-supported CoFe@Fe3O4 alloy catalyst material with a core-shell structure.

[0036] Example 2

[0037] This embodiment is basically the same as Embodiment 1, except that:

[0038] In this embodiment, a method for preparing a defect-rich carbon-supported Co catalyst material having a core-shell structure comprises the following steps:

[0039] Step 1: 1 mmol (256 mg) of cobalt acetylacetonate and 0 mmol (0 mg) of iron acetylacetonate were ultrasonically dispersed in triethylene glycol; the mixture was heated to 110°C and kept warm for 30 min; then the temperature was raised to 250°C and kept warm for 60 min; finally, it was cooled to room temperature, washed by centrifugation with ethyl acetate and freeze-dried to obtain a sample of Co3O4;

[0040] Step 2: Same as Example 1, obtaining layered g-C3N4;

[0041] Step 3: The same as in Example 1, obtaining a g-C3N4 / Co3O4 composite material;

[0042] Step 4: Different from Example 1, a defect-rich carbon-supported Co catalyst material with a core-shell structure is obtained.

[0043] Example 3

[0044] This embodiment is basically the same as the above embodiment, with the following features:

[0045] In this embodiment, a method for preparing a defect-rich carbon-supported Fe3O4 catalyst material having a core-shell structure comprises the following steps:

[0046] Step 1: Take 0mmol (0mg) of cobalt acetylacetonate and 1mmol (353mg) of iron acetylacetonate and disperse them in triethylene glycol by ultrasonication; heat the mixture to 110°C and keep it warm for 30min; then increase the temperature to 250°C and keep it warm for 60min; finally cool to room temperature, wash with ethyl acetate by centrifugation and freeze-dry to obtain sample Fe3O4;

[0047] Step 2: Same as Example 1, obtaining layered g-C3N4;

[0048] Step 3: The same as in Example 1, obtaining a g-C3N4 / Fe3O4 composite material;

[0049] Step 4: Different from Example 1, a defect-rich carbon-supported Fe3O4 catalyst material with a core-shell structure is obtained.

[0050] Example 4

[0051] This embodiment is basically the same as the above embodiment, with the following features:

[0052] In this embodiment, a method for preparing a defect-rich carbon-supported CoFe@Fe3O4 alloy catalyst having a core-shell structure comprises the following steps:

[0053] Step 1: same as in Example 1, obtaining a sample CoFeO4;

[0054] Step 2: Same as Example 1, obtaining layered g-C3N4;

[0055] Step 3: The same as in Example 1, obtaining a g-C3N4 / CoFeO4 composite material;

[0056] Step 4: anneal the material obtained in step 3 in a mixture of CO2 and H2, wherein the H2 in the mixture is 50 vol%, the balance gas is Ar, the annealing temperature is 450°C, and the temperature is kept for 1 hour; after cooling to room temperature, a defect-rich carbon-supported CoFe@Fe3O4 alloy catalyst material with a core-shell structure can be obtained.

[0057] Example 5

[0058] This embodiment is basically the same as the above embodiment, with the following features:

[0059] In this embodiment, a method for preparing a defect-rich carbon-supported CoFe@Fe3O4 alloy catalyst having a core-shell structure comprises the following steps:

[0060] Step 1: Using a wet chemical method, 1 mmol of cobalt acetylacetonate and 2 mmol of iron acetylacetonate are ultrasonically dispersed in triethylene glycol; the mixed solution is heated to 110°C and kept warm for 30 minutes; then the temperature is increased to 250°C and kept warm for 60 minutes; finally, it is cooled to room temperature, washed by centrifugation with ethyl acetate and freeze-dried to obtain a sample CoFeO4 precursor material;

[0061] Step 2: Same as Example 1, obtaining layered g-C3N4;

[0062] Step 3: The same as in Example 1, obtaining a g-C3N4 / CoFeO4 composite material;

[0063] Step 4: Same as Example 1, obtain a defect-rich carbon-supported CoFe@Fe3O4 alloy catalyst material with a core-shell structure.

[0064] Example 6

[0065] This embodiment is basically the same as the above embodiment, with the following features:

[0066] In this embodiment, a method for preparing a defect-rich carbon-supported CoFe@Fe3O4 alloy catalyst having a core-shell structure comprises the following steps:

[0067] Step 1: Using a wet chemical method, 2 mmol of cobalt acetylacetonate and 1 mmol of iron acetylacetonate are ultrasonically dispersed in triethylene glycol; the mixed solution is heated to 110°C and kept warm for 30 minutes; then the temperature is increased to 250°C and kept warm for 60 minutes; finally, it is cooled to room temperature, washed by centrifugation with ethyl acetate and freeze-dried to obtain a sample CoFeO4 precursor material;

[0068] Step 2: Same as Example 1, obtaining layered g-C3N4;

[0069] Step 3: The same as in Example 1, obtaining a g-C3N4 / CoFeO4 composite material;

[0070] Step 4: Same as Example 1, obtain a defect-rich carbon-supported CoFe@Fe3O4 alloy catalyst material with a core-shell structure.

[0071] Experimental test analysis:

[0072] Conduct material characterization analysis:

[0073] 1. X-ray diffraction analysis was performed on the materials of the above examples, and the results were as follows: Figure 1 As shown, different products can be obtained for different CoFe ratios. Examples 1-4 correspond to CoFe@Fe3O4, Co element, Fe3O4 and CoFe@Fe3O4, respectively. The product obtained in Example 1 was analyzed by transmission electron microscopy (TEM) and electron energy loss spectroscopy (EELS). The results are shown in FIG. Figure 2 As shown, it can be seen that nanoparticles with a core-shell structure of 25nm in diameter are distributed on the carbon carrier, where the shell thickness is 2nm. The core-shell structure was further analyzed for composition. EELSmapping and line scan structure showed that the shell is composed of iron oxide and the internal core is composed of CoFe alloy. In order to further determine the phase structure of the material, selected area electron diffraction (SAED) analysis was performed, and the results are shown in Figure 3 As shown, the material contains α-C, Fe3O4 and CoFe alloy. At the same time, the material of Example 1 was characterized by Raman spectroscopy, and the results are as follows Figure 4 As shown, it can be seen that the ratio of the D peak to the G peak is 0.82, indicating that the carbon material contains a large number of defects, which contribute to the adsorption and activation of CO2 in the catalytic reaction. Combining the analysis of XRD, TEM, EELS, SAED and Raman, it can be clearly concluded that the material synthesized in Example 1 is a CoFe alloy with a core diameter of 20nm and a Fe3O4 with a shell thickness of 2nm. The CoFe@Fe3O4 is uniform in size and evenly distributed on the defect-rich carbon support.

[0074] 2. Catalyst performance evaluation:

[0075] The CO2 hydrogenation performance of the samples of Examples 1-3 was evaluated by the following test method: 20 mg of the catalyst was placed between two layers of quartz wool in the center of a quartz tube (inner diameter 6 mm). Before the catalytic test, the catalyst was heated at normal pressure with a reaction gas (H2 / CO2 / Ar = 2.5 / 2.5 / 5 mL / min -1 ,WHSV=30000mLh -1 gcat -1 ) was pretreated at 450℃ for 1h. Then the catalytic performance at different temperatures (250-500℃) was tested under the same reaction atmosphere, and the products were analyzed by online gas chromatograph (GC7900Ⅱ, Tianmei, China), which was equipped with TDX-01 column, thermal conductivity detector and flame ionization detector. The test results are shown in Figure 5As shown, it can be seen that CoFe@Fe3O4 supported on defect-rich carbon has the best catalytic activity, with a CO2 conversion rate of 30% and a CO selectivity of 99%. In contrast, the single element has poor catalytic performance, with a CO2 conversion rate of only 5% for single element Co and a conversion rate of 25% for single element Fe3O4, but a CO selectivity of only 78%. By comparison, it can be concluded that the dual-element CoFe@Fe3O4 has the best CO2 hydrogenation catalytic performance.

[0076] The defect-rich carbon-supported CoFe@Fe3O4 alloy CO2 hydrogenation catalyst with a core-shell structure of Examples 1 and 4-6, and its preparation method and application, the prepared catalyst core is a CoFe alloy with a diameter of 20nm, the shell is a Fe3O4 with a thickness of 2nm, and is uniformly loaded on the defect-rich carbon support without sintering and agglomeration. In addition, the material of the present invention exhibits excellent catalytic activity when used as a CO2 hydrogenation catalyst, with a CO2 conversion rate of 30% and a CO selectivity of 99% at 450°C, and the material itself is pollution-free and easy to synthesize, and can be well applied to technical fields such as energy materials.

[0077] The above describes the embodiments of the present invention in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made according to the purpose of the invention. Any changes, modifications, substitutions, combinations or simplifications made according to the spirit and principle of the technical solution of the present invention should be equivalent replacement methods. As long as they meet the purpose of the invention and do not deviate from the technical principles and inventive concepts of the present invention, they belong to the protection scope of the present invention.

Claims

1. A method for preparing a CoFe@Fe3O4 alloy CO2 hydrogenation catalyst having a core-shell structure, characterized in that: Using CoFe2O4 and g-C3N4 as precursor materials, a catalyst material of CoFe alloy with a core diameter of 5-25nm and Fe3O4 with a shell thickness of 1-5nm supported on a defect-rich carbon carrier is prepared by a heat treatment method as a catalyst material for CO2 hydrogenation reaction; The preparation method of the CoFe@Fe3O4 alloy CO2 hydrogenation catalyst comprises the following steps: Step 1: Prepare CoFe2O4 by wet chemical method, with the molar ratio of CoFe element to be prepared being 1:2; Step 2: Prepare g-C3N4 by thermal polymerization, and then subject it to ultrasonic exfoliation with an ultrasonic power of 100-500 W. Centrifuge and take the supernatant to prepare layered g-C3N4. Step 3: Loading the CoFe2O4 prepared in step 1 on the layered g-C3N4 prepared in step 2, so that the CoFe2O4 loading amount is not higher than 30 wt%, to obtain a g-C3N4 / CoFe2O4 composite material; Step 4: The g-C3N4 / CoFe2O4 composite material prepared in step 3 is annealed in a mixture of CO2 and H2. Calculated by volume percentage, the H2 in the mixture is 25-50 vol%, the CO2 is 0-25 vol%, and the balance gas is Ar. The CO2 content in the mixture is not zero. The annealing temperature is 300-600°C. After cooling to room temperature, a CoFe@Fe3O4 alloy CO2 hydrogenation catalyst with a core-shell structure is obtained.

2. The method for preparing the CoFe@Fe3O4 alloy CO2 hydrogenation catalyst having a core-shell structure according to claim 1, characterized in that: A catalyst material with a core diameter of 20nm CoFe alloy and a shell thickness of 2nm Fe3O4 supported on a defect-rich carbon support was prepared.

3. The method for preparing the CoFe@Fe3O4 alloy CO2 hydrogenation catalyst having a core-shell structure according to claim 1, characterized in that: In the step 1, no more than 2 mmol of cobalt acetylacetonate and no more than 2 mmol of iron acetylacetonate are weighed and ultrasonically dispersed in triethylene glycol; the mixed solution is heated to no more than 110° C. and kept warm for at least 30 min; then the temperature is increased to no more than 250° C. and kept warm for at least 60 min; then cooled to room temperature, washed by centrifugation with ethyl acetate and freeze-dried to obtain CoFe2O4.

4. The method for preparing the CoFe@Fe3O4 alloy CO2 hydrogenation catalyst having a core-shell structure according to claim 1, characterized in that: In the above step 2, at least 10 g of urea is weighed and placed in a 50 mL crucible, and the temperature is raised to not less than 550°C at a heating rate of not less than 2.3°C / min and kept warm for at least 4 hours to carry out a thermal polymerization reaction; the product is then ultrasonically stripped at an ultrasonic power of 100-500 W; the supernatant is then freeze-dried to obtain layered g-C3N4.

5. The method for preparing the CoFe@Fe3O4 alloy CO2 hydrogenation catalyst having a core-shell structure according to claim 1, characterized in that: In the above step 3, at least 100 mg of layered g-C3N4 is ultrasonically dispersed in deionized water; then 5-30 mg of CoFe2O4 is added and ultrasonicated for 1 h; freeze-dried to obtain a g-C3N4 / CoFe2O4 composite material.

6. A CoFe@Fe3O4 alloy CO2 hydrogenation catalyst with a core-shell structure, characterized in that: The catalyst is prepared by the method for preparing the CoFe@Fe3O4 alloy CO2 hydrogenation catalyst with a core-shell structure as described in claim 1.

7. The CoFe@Fe3O4 alloy CO2 hydrogenation catalyst with a core-shell structure according to claim 6, characterized in that: The CoFe@Fe3O4 nanoparticles with core-shell structure are uniform in size, and the CoFe@Fe3O4 nanoparticles are evenly distributed on the defect-rich carbon support to form a composite material structure.

8. An application of the CoFe@Fe3O4 alloy CO2 hydrogenation catalyst having a core-shell structure as claimed in claim 6, characterized in that: The CoFe@Fe3O4 alloy CO2 hydrogenation catalyst with core-shell structure is used as the catalyst material for CO2 hydrogenation reaction.

Citation Information

Patent Citations

  • Multilevel core-shell structure magnetic nano gold catalyst and preparation method thereof

    CN102513126A

  • Carbon nitride nanosheet (CNNS) composite pH-sensitive hydrogel with Pizza structure as well as preparation method and application of CNNS composite pH-sensitive hydrogel

    CN110813346A